Dry needling in sports and sport recovery: a systematic review with an evidence gap map - Kuzdzal, A.; Trybulski, R.; Muracki, J.; Klich, S.; Clemente, F. M.; Kawczynski, A. (Sports Medicine, 2025)
Background: Dry needling is an increasingly popular technique used in sports and regenerative medicine contexts. However, there is no comprehensive overview of investigations of dry needling in sports and sport recovery. Objectives: The objectives were to perform a systematic review of dry needling in sports athletes with an evidence gap map, to identify current gaps in the literature, and to provide stakeholders with direction for future research. Methods: Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 guidelines were followed. Studies on healthy and injured athletes receiving dry needling were included. Three databases (PubMed, Scopus, and Web of Science) were searched, data were synthesized narratively, key data were summarized quantitatively, and an evidence gap map was created. Results: The authors incorporated 24 studies into the current study, encompassing 580 athletes, predominantly involving talent/developmental and highly trained/national-level athletes across 13 sports. Most studies used passive or placebo controls, with 37.5% incorporating active controls. Interventions focused mainly on the lower limbs (58.3%). Around 69% of studies reported pain perception outcomes, while six examined muscular strength, activity, and range of motion. While results varied, dry needling generally showed a more positive effect on pain than on athletic performance. Conclusions: Dry needling studies seem to describe general effectiveness and safety for reducing pain and muscle stiffness in a wide variety of body regions. However, further research is needed on underrepresented populations such as elite, world-class, and Paralympic athletes, as well as expanding investigations into long-term effects and a broader range of muscle groups, particularly the hamstrings. The results may be valuable for medical professionals, sports medicine specialists, and researchers.